Reconnaisance in Esmeraldas - Ferguson Tichy, Marjorie (1941)
A rare group of clay specimens came to light recently in the process of cataloging the archaeological material from the ruins of Otowi, New Mexico, acquired by, the Museum of New Mexico from the Philadelphia Commercial Museum, which conducted excavations there in 1916 and 1917, under an arrangement with the New Mexico institution. Among the several hundred clay vessels, consisting largely of Abiquiu, Bandelier black on grey and Tsankawi black on cream, dark culinary vessels, Potsuwi-i incised and a few Rio Grande glaze decorated pieces, hundreds of interesting artifacts and ceremonial pieces of stone, bone, and wood, were six actual Biscuit ware “biscuits.” These interesting little objects were undoubtedly gaming pieces, the writer believes. Their size and shape must, first of all, exclude them from any practical every day usage, such as our so called “pot lids.” While possessing the same general superficial characteristics each one is unique in detail.